Task Complexity and the Complexity of Written Language Production: A Review of Literature - Nik Aloesnita, Nik Mohd Alwi; Umi Kalsom, Masrom; Nor Shidrah, Mat Daud (Macrothink Institute, 2015)
Robinson’s Cognition Hypothesis (Robinson 2001a, 2003a, 2003b, 2005, 2007a, 2007b) predicts that more cognitively complex tasks along resource-directing dimension will lead to greater complexity of language production while cognitively complex tasks along resource-dispersing dimension will result in less complex language production. Various studies have investigated the effects of manipulating variables on these dimensions (i.e. resource-directing and resource-dispersing) either in oral or written language production. This paper compares and contrasts the results of several studies that were conducted by manipulating these variables in written language production. It also suggests guidelines for future research studies in this area. It concludes that further studies are necessary to investigate how language teachers can integrate and manipulate task-based instruction in their classrooms.